2015
DOI: 10.1159/000381051
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Dysplasias: An Overview

Abstract: Constitutional disorders of bone, commonly termed skeletal dysplasias (SDs), are inherited disorders of cartilage and/or bone that affect their growth, morphometry and integrity. Associated skeletal abnormalities are usually but not invariably symmetrical. They may be classified as osteochondrodysplasias, which are conditions associated with abnormalities of the growth (dysplasias) or texture (osteodystrophy) of bone and/or cartilage, or dysostoses, which are conditions secondary to abnormal blastogenesis (occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…Therefore, our findings suggest that BMP4 may be essential for maintaining normal human bone density. Similar to tooth agenesis, familiar osteoporosis also has a strong genetic predisposition (Offiah, 2015). Loss-of-function mutations of proteins in the Wnt pathway, WNT1 (Kampe, Makitie, & Makitie, 2015) and LRP5 (Biha, Ghaber, Hacen, & Collet, 2016), have been shown to cause juvenile osteoporosis, while a heterozygous duplication of BMP2 (Su et al, 2011) was found in a patient with brachydactyly, a congenital deformity of the digits.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings suggest that BMP4 may be essential for maintaining normal human bone density. Similar to tooth agenesis, familiar osteoporosis also has a strong genetic predisposition (Offiah, 2015). Loss-of-function mutations of proteins in the Wnt pathway, WNT1 (Kampe, Makitie, & Makitie, 2015) and LRP5 (Biha, Ghaber, Hacen, & Collet, 2016), have been shown to cause juvenile osteoporosis, while a heterozygous duplication of BMP2 (Su et al, 2011) was found in a patient with brachydactyly, a congenital deformity of the digits.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small part of these disorders has clear molecular pathogenesis [5]. Moreover, skeletal involvement may also occur in other multisystem syndromes [6]. Therefore, due to the clinical and genetic heterogeneity of SDs, it is very challenging to make a clear diagnosis, particularly in the prenatal diagnosis of fetal SDs.…”
Section: Introductionmentioning
confidence: 99%
“…These are most useful over 8 weeks gestation, given the lack of skeletal ossification prior to this age [51]. It is also important to remember that although isolated limb anomalies may be more commonly encountered in live cases [52], lethal skeletal dysplasias will be more prevalent in the subgroup presenting for post-mortem imaging [53] so an entire overview of the body is usually necessary rather than imaging of the affected limb(s). Whilst PMUS can be useful in demonstrating the non-ossified, cartilaginous anatomy which is not present on radiography (Fig.…”
Section: Systems Reviewmentioning
confidence: 99%